2018
DOI: 10.1002/bmc.4161
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of residues of metalaxyl, cyazofamid and a cyazofamid metabolite in tobacco leaves and soil by liquid chromatography with tandem mass spectrometry

Abstract: A simple method was developed and validated for the simultaneous determination of metalaxyl, cyazofamid and the cyazofamid metabolite 4-chloro-5-p-tolylimidazole-2-carbonitrile (CCIM) by liquid chromatography with tandem mass spectrometry. The three target compounds were extracted from tobacco and soil with acetonitrile containing 0.1% acetic acid, and the extracts were purified using octadecylsilane. The proposed method showed satisfactory linearity (R ≥ 0.9985) for the target compounds. The limits of detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…When the ME value is <1, the analyte response is suppressed. When the ME value equals 1, no matrix effects have occurred (Wu et al, 2018). The data in The highest response value was obtained when the combination sequence was A3B2C1D3, which was consistent with the optimized pretreatment condition of the three compounds.…”
Section: Methods Validationsupporting
confidence: 75%
See 2 more Smart Citations
“…When the ME value is <1, the analyte response is suppressed. When the ME value equals 1, no matrix effects have occurred (Wu et al, 2018). The data in The highest response value was obtained when the combination sequence was A3B2C1D3, which was consistent with the optimized pretreatment condition of the three compounds.…”
Section: Methods Validationsupporting
confidence: 75%
“…When the ME value is <1, the analyte response is suppressed. When the ME value equals 1, no matrix effects have occurred (Wu et al, ). The data in Table show that the MEs in brown rice, paddy plants and rice hulls were suppressing TFSA and TEB signals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have already shown that CCIM appears to be more acutely toxic than cyazofamid ( European Food Safety Authority 2016). LC as well as LC–MS have been used to analyse cyazofamid and CCIM. Dissipation of cyazofamid has been determined in tobacco and tomato .…”
Section: Introductionmentioning
confidence: 99%
“…LC as well as LC–MS have been used to analyse cyazofamid and CCIM. Dissipation of cyazofamid has been determined in tobacco and tomato . But field trials have seldom conducted for simultaneous determination of pyraclostrobin, cyazofamid and CCIM.…”
Section: Introductionmentioning
confidence: 99%